2010
DOI: 10.4049/jimmunol.0904182
|View full text |Cite
|
Sign up to set email alerts
|

TCRβ Allelic Exclusion in Dynamical Models of V(D)J Recombination Based on Allele Independence

Abstract: Material Supplementary 2.DC1http://www.jimmunol.org/content/suppl/2010/06/28/jimmunol.090418

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
(126 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have shown that chromatin remodelling and transcription of the Ig and TCR loci is important for successful recombination and allelic exclusion of the unused gene rearrangement262728. Epigenetic modification may also be an important factor in determining the order of rearrangement for the two chromosomes, as unequal methylation levels at the onset of recombination could delay the rearrangement of the methylated chromosome29. In this paper, we observed an increase in variance when comparing chromosomal usage ratios in productive versus non-productive sequences, consistent with a model where one chromosome is preferentially rearranged 1.5-fold more often (on average).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that chromatin remodelling and transcription of the Ig and TCR loci is important for successful recombination and allelic exclusion of the unused gene rearrangement262728. Epigenetic modification may also be an important factor in determining the order of rearrangement for the two chromosomes, as unequal methylation levels at the onset of recombination could delay the rearrangement of the methylated chromosome29. In this paper, we observed an increase in variance when comparing chromosomal usage ratios in productive versus non-productive sequences, consistent with a model where one chromosome is preferentially rearranged 1.5-fold more often (on average).…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly recognized that cell fate decisions and underlying genetic circuits are subjected to such stochastic fluctuations to generate non‐genetic cellular diversity; with, in mammals, intrinsic noise in gene expression mainly depending on epigenetic‐regulated chromatin changes . When integrated at the level of a whole cell‐population, this model makes it possible to readily predict the distinct TCRβ cell genotypes and allelic exclusion/inclusion profiles from wild‐type and mutant mice . In keeping with the same concepts, we anticipate that corresponding features at other gene loci could likewise be interpreted.…”
Section: The Control Of Allelic Exclusion: Deterministic Stochastic mentioning
confidence: 77%
“…On the other hand, highly stochastic scenarios are hard to reconcile with the relatively high proportion (40–45%) of cells displaying fully rearranged, productive and non‐productive, IgH or TCRβ alleles. Using TCRβ allelic exclusion as a reference system, we proposed that a dynamic combination of the two concepts, determinism and stochasticity – as modelled using the Markov chain formalism, better accounts for the distribution of TCRβ genotypes emerging from early T‐cell development; (Fig. b,c).…”
Section: The Control Of Allelic Exclusion: Deterministic Stochastic mentioning
confidence: 99%
“…However, interallelic crosstalk cannot fully explain H chain exclusion in the shark since linked IgH and their alleles rearrange independently of each other. Perhaps more relevant to the shark observations is a model recently generated for the TCRβ locus, which proposes that if the two alleles are autonomous and activated stochastically they are unlikely to initiate recombination at the same time [10]. A sufficient time lag between the two steps, D to J and V to DJ, would permit a productive VDJ at the first allele to effect inhibition on the second, rearranging allele.…”
Section: Discussionmentioning
confidence: 99%
“…Both alleles are poised for rearrangement, but it is the asynchrony at the VH to DJ step that initiates allelic exclusion and events leading to a single type of antigen receptor expressed per lymphocyte. The underlying causes for one gene acting ahead of the other are the subject of some controversy [810]. …”
Section: Introductionmentioning
confidence: 99%